Pengaruh Harga, Kurs Dollar Amerika Serikat dan Produksi Terhadap Ekspor Vanili di Provinsi Bali Tahun 1991-2013 - Widya Chandrayani, Putu Maya; Natha, Ketut Suardhika (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 2, Februari 2016 (pp. 216 - 315), 2016)
Indonesia is a developing country that is being intensively implement international trade is the export of plantation crops. One crop that became the belle of the commodities vanilla (Vanilla Planifolia Andrews) one of which is located in the province of Bali. This study aimed to analyze the effect of prices, the US dollar exchange rate and production for export of vanilla in the province of Bali. The data used in this research is secondary data. Data collected by non-participant observation, then the data is processed by multiple linear regression analysis techniques that were previously equipped with the classical assumption. Test results to obtain the results of the price, US dollar exchange rate and production simultaneously have a significant effect on exports of vanilla in the province of Bali. Partially price positive and significant impact on exports of vanilla, the US dollar exchange rate has no effect on the export of vanilla and production and significant positive effect. R2 value in this study was 0.633, or 63.3 percent, and the remaining 36.7 percent is influenced by other variables that are not described in the study.
Keywords: export, price, US dollar exchange rate, production